Optimization of tip material and shape for near-UV TERS in Si structures - Poborchii, Vladimir; Tada, Tetsuya; Kanayama, Toshihiko; Geshev, Pavel (Journal of Raman spectroscopy, 2009)
High spatial resolution stress mapping of Si device structures is in high demand throughout electronic industry. This problem can be solved by application of the tip‐enhanced Raman scattering (TERS) to Si structures. This work involves searching for a suitable TERS material for the near‐UV spectral range that is favorable for Raman mapping of Si structures. We show both theoretically and experimentally that Al is a good Raman enhancer at the 363.8 nm wavelength. Taking into account Raman selection rules of Si and high dielectric contrast between Si and air, we employed an inclined Al‐coated Si atomic force microscope (AFM) tip that is also suitable for the top‐illumination geometry of the experiment. We succeeded in detecting of a weak TERS signal of strained Si. Possible ways of improvement of the Si TERS signal/noise ratio are discussed. An Al‐particle‐topped AFM tip is considered as a promising solution to the problem. A prototype tip was fabricated. Copyright © 2009 John Wiley & Sons, Ltd. We demonstrate both theoretically and experimentally that Al is an efficient SERS/TERS material at the 364 nm wavelength, most suitable for Raman and stress mapping of Si structures. An inclined Al‐coated AFM tip was employed for TERS study of strained Si, a weak TERS signal being detected. Ways of its improvement are discussed.